2004
DOI: 10.1074/jbc.m312938200
|View full text |Cite
|
Sign up to set email alerts
|

Observation and Characterization of the Interaction between a Single Immunoglobulin Binding Domain of Protein L and Two Equivalents of Human κ Light Chains

Abstract: Protein L is a multidomain cell wall bound protein found in ϳ10% of the Peptostreptococcal isolates (1) and contains a series of repeated domains, some of which are able to bind to immunoglobulins without initiating an immune response. Expression of this protein has been correlated to the virulence of these opportunistic pathogenic bacteria (1) that are found in the gastrointestinal and urogenital tracts (2). Its presence has been found to cause cellular responses such as histamine release from basophils and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 16 publications
(22 reference statements)
1
20
1
Order By: Relevance
“…In addition, in the B cell receptor of hairy cell leukemia chains has been shown to be preferentially used (23). Yet another well-established functional difference between and antibodies is the interaction of chains with the bacterial surface protein L (20,24). It has also been demonstrated that the isotype of the IGL chain can influence the kinetics of the intracellular assembly of antibodies and the susceptibility of the interchain disulfide bonds to reducing agents (25).…”
Section: Genementioning
confidence: 99%
“…In addition, in the B cell receptor of hairy cell leukemia chains has been shown to be preferentially used (23). Yet another well-established functional difference between and antibodies is the interaction of chains with the bacterial surface protein L (20,24). It has also been demonstrated that the isotype of the IGL chain can influence the kinetics of the intracellular assembly of antibodies and the susceptibility of the interchain disulfide bonds to reducing agents (25).…”
Section: Genementioning
confidence: 99%
“…6,9 Its existence has recently been confirmed by a combination of mutagenesis, stopped-flow fluorescence (SFF) and isothermal titration calorimetry (ITC). 10 Both methods, SFF and ITC reveal the site 2 affinity for huVkI in C* to be approximately 100-fold lower than site 1. However, it is unclear if that differential is maintained for different B and C domains and their binding to different Vk subtypes.…”
Section: Discussionmentioning
confidence: 98%
“…These studies also hinted at the existence of a second, low affinity Ig binding site on PpL, which has now been confirmed by other methods. 10,11 Recombinant PpL (4-domains) is commercially available (Affitech, Norway) and a highly sensitive reagent for the detection of human Vk chains, superior to for example commonly used antipeptide tag antibodies. 12 However, higher affinity Ig binding domains would be desirable reagents for many biotechnological applications including for increased sensitivity in immunoassays such as enzyme-linked immunosorbant assays (ELISAs) and Western blots or as capture reagents for antibody arrays.…”
Section: Introductionmentioning
confidence: 99%
“…Only two mutants gave usable data even if crystals were also obtained with other mutants. The single-site mutant L57H that was shown by calorimetry and stopped-flow fluorescence to have reduced site 1 affinity (Housden et al, 2004) gives peptide-complexed crystals at low pH, while PpL mutant H74C, that can bind at both site 1 and site 2, gives the same packing but at high pH with NaCl added. This may be due to the His to Cys mutation, but in order to separate out all the possibilities more trials would be needed.…”
Section: Discussionmentioning
confidence: 99%
“…1a). The additional L57H mutation weakens PpL site 1 binding (Housden et al, 2004) and thus it may help slow down the crystallization. A reduction in MPEG concentration is also implemented to achieve the same goal.…”
Section: Crystals With Peptide 2-45mentioning
confidence: 99%